2009
DOI: 10.1074/jbc.m901568200
|View full text |Cite
|
Sign up to set email alerts
|

TEADs Mediate Nuclear Retention of TAZ to Promote Oncogenic Transformation

Abstract: The transcriptional coactivators YAP and TAZ are downstream targets inhibited by the Hippo tumor suppressor pathway. The expression level of TAZ is recently shown to be elevated in invasive breast cancer cells and some primary breast cancers. TAZ is important for breast cancer cell migration, invasion, and tumorigenesis, but the underlying mechanism is not defined. In this study, we show that TAZ interacts with TEAD transcriptional factors. Knockdown of TEADs suppresses TAZmediated oncogenic transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 57 publications
9
216
0
Order By: Relevance
“…Previous studies have mapped the TBD of YAP to a small N-terminal region containing residues 48-102 ( Fig. 1A) (30,31). We expressed a large fragment of YAP (residues 2-268) containing the TBD and the two WW domains, labeled it with 15 N, and acquired a 2D 1 H∕ 15 N heteronuclear single quantum correlation (HSQC) spectrum ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mapped the TBD of YAP to a small N-terminal region containing residues 48-102 ( Fig. 1A) (30,31). We expressed a large fragment of YAP (residues 2-268) containing the TBD and the two WW domains, labeled it with 15 N, and acquired a 2D 1 H∕ 15 N heteronuclear single quantum correlation (HSQC) spectrum ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demon- strated that the Hippo pathway inhibits TAZ by promoting cytoplasmic localization via Ser-89 phosphorylation, which generates a 14-3-3 binding site (15). This provides a mechanism of spatial separation of TAZ by sequestering it away from its nuclear target transcription factors, such as TEAD (26,33). In this study we revealed another mechanism, SCF ␤-TrCP -mediated ubiquitylation and 26 S proteasome-dependent degradation, for the regulation of TAZ by the Hippo pathway via protein stability control.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to modulate transcription of downstream cellular genes, TAZ requires interactions with transcription factors through its TBD or WW (W, tryptophan) domain. Previous studies have shown that TAZ interacts with members of the TEAD family of transcription factors (TEAD1-4) through seven conserved residues in the TBD of TAZ (23,28). Among these, two phenylalanine residues located at positions 52 and 53 (Phe-52/53) were shown to be critical for TAZ-TEAD binding.…”
Section: Tbd Is Necessary For Taz-induced Negativementioning
confidence: 99%